Usability Study of the iACTwithPain Platform: An Online Acceptance and Commitment Therapy and Compassion-Based Intervention for Chronic Pain - Guiomar, Raquel; Trindade, Inês A.; Carvalho, Sérgio A.; Menezes, Paulo; Patrão, Bruno; Nogueira, Maria Rita; Lapa, Teresa; Duarte, Joana; Pinto-Gouveia, José; Castilho, Paula (Frontiers in Psychology, 2022)
Background: This pilot study aims to test the usability of the iACTwithPain platform, an online ACT-based intervention for people with chronic pain, to obtain information on which intervention and usability aspects need improvement and on expected retention rates. Methods: Seventy-three Portuguese women with chronic pain were invited to complete the first three sessions of the iACTwithPain intervention assess their quality, usefulness and the platform's usability. Twenty-one accepted the invitation. Additionally, eight healthcare professionals working with chronic medical conditions assessed the platform and the intervention from a practitioner's point of view. Results: This study presented a considerable attrition rate (71.43%) among chronic pain participants, with six completers. There were no significant differences in demographic or clinical variables between dropouts and completers except for completed education (participants who dropped out presented less education than completers). Reasons for dropout were related to difficult personal events occurring during the time of the intervention, lack of time, or having forgotten. There seemed to be an overall satisfaction with both the intervention, its contents and form of presentation of information, and the platform, concerning its design, appearance, and usability. Real image videos were preferred over animations or audio by chronic pain participants. Healthcare professionals emphasized the appealing and dynamic aspects of the animation format. Conclusions: This study informs the ongoing improvement of the iACTwithPain platform and provides valuable information on aspects researchers should consider while developing online psychological interventions for chronic pain. Further implications are discussed.